2013
DOI: 10.1186/1743-8977-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of silver-nanoparticles and silver-ions to lung cells in vitro at the air-liquid interface

Abstract: BackgroundDue to its antibacterial properties, silver (Ag) has been used in more consumer products than any other nanomaterial so far. Despite the promising advantages posed by using Ag-nanoparticles (NPs), their interaction with mammalian systems is currently not fully understood. An exposure route via inhalation is of primary concern for humans in an occupational setting. Aim of this study was therefore to investigate the potential adverse effects of aerosolised Ag-NPs using a human epithelial airway barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
93
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 58 publications
14
93
2
Order By: Relevance
“…According to the results in this study, silver ions caused the loss of cell membrane integrity in a dose-dependent manner, while AgNPs did not compromise it in the tested concentration range (0.01-10 mg/ mL). Similar finding was also reported in lung cells, wherein the cellular integrity was not impaired upon agglomerates of AgNPs exposure, but was damaged by a higher concentrated AgNO 3 solution (Herzog et al, 2013). This implied the occurrence of distinct toxicological events in astrocytes stimulated by cytotoxic levels of these two silver species, i.e.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…According to the results in this study, silver ions caused the loss of cell membrane integrity in a dose-dependent manner, while AgNPs did not compromise it in the tested concentration range (0.01-10 mg/ mL). Similar finding was also reported in lung cells, wherein the cellular integrity was not impaired upon agglomerates of AgNPs exposure, but was damaged by a higher concentrated AgNO 3 solution (Herzog et al, 2013). This implied the occurrence of distinct toxicological events in astrocytes stimulated by cytotoxic levels of these two silver species, i.e.…”
Section: Discussionsupporting
confidence: 70%
“…However, this viewpoint still remains ambiguous as inconsistent evidences are often provided from different scenarios. Substantial comparative toxicity assessments have accordingly been performed using diverse experimental models in vitro and in vivo for diverse AgNPs and silver ions (Bone et al, 2015;Herzog et al, 2013). Most of the studies revealed that ionic silver species caused relatively higher toxicity than AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“…occupational exposures at the workplace or biomedical applications, it is crucial to address the biological effects upon repeated CNTs exposure. Consequently, the aim of this study was to mimic inhalation of CNTs in vitro and reveal the mechanisms that underlay the manifestation of potential adverse effects, by producing MWCNTs aerosols using the Air-Liquid Interface Cell Exposure System (ALICE) as described by Lenz et al (2009) for spherical ZnO nanoparticles (NPs), as well as gold NPs ) and silver NPs (Herzog et al, 2013). Recently, it has further been highlighted as a reliable system for the aerosolisation of high aspect ratio materials such as cellulose nanocrystals .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Recent work by Herzog et al, has also demonstrated the biocompatibility of silver nanoparticles with airway epithelial cells. [8] In this study, we tested the combination of AgNP with CSG -LL37 peptide, where the -SH served as stabilizer on the AgNP surface [9] forming LL37@AgNP as a new antimicrobial and anti-biofilm agent. Details of the LL37 synthesis are in SI.…”
mentioning
confidence: 99%